A Comparative Analysis of the Missing (Mafqud) Husband Regulations in Indonesia and Malaysia: A Study to Reform the Regulation That Meets Legal Certainty in Indonesia - Farahsyinta Gladisia Puspa Fardiana; Khoirul Hidayah; Mohd Hazim bin Borhan (Fakultas Syariah, 2022)
This article aims to resolve legal issues regarding missing (mafqud) husbands in Indonesia and to provide input for revising these laws to better provide protection to wives whose husbands are missing in keeping with the principle of legal certainty. There are two circumstances when the husband leaves the house, the first is the husband leaves his house without his wife's permission but his whereabouts are still known, this condition is called absent husband or ghaib husband. The second circumstance is the husband leaves the house with the wife's permission, but his whereabouts and life and death are unknown, which is often called the missing husband or mafqud husband. The differences in the circumstances of the husband's departure from home require different verdicts in the dissolution of marriages. The regulation of the missing (mafqud) husband in Indonesia has not been differentiated from the regulation of absent (ghaib) husband so there is no regulation that regulates the death determination for the missing (mafqud) husband to dissolve the marriage in Indonesia. This article is a normative juridical study using a statute and comparative approaches. The results of this article indicate the need to legislate for missing (mafqud) husbands that provide legal certainty for women. The regulation of missing (mafqud) husbands in Indonesia that can provide legal certainty for women is to set a minimum limit of four years for a husband to leave the home to be determined his death as stipulated in section 53 of the 1984 Islamic Family Act (Federal Territory) 1984.